Estudos das queixas auditivas, extra auditivas e achados audiométricos nos professores de uma academia de ginástica - Côrtes, Isabela Freixo (2006)
Objective: The aim of this research was to study auditory and extra-auditory complaints of physical education teachers exposed to electronically amplified music, to describe the audiometric findings and to investigate the influence of the variables, time in the profession, work-journey and the presence of audiometric notch. Method: A number of 32 teachers were evaluated, aged from 21 to 35 years old, with at least one year of working and daily exposition of four hours to electronically amplified music. Besides occupational and clinical anamnesis pure tone thresholds were analyzed according to the presence of audiometric notch. Results: Most of the teachers (87,5%) have had extra-occupational exposure. The most frequent complaints were dizziness (12,5%); irritability and nervousness (28,1%); insomnia (31,3%); headache (37,5%); tinnitus (28,10%); aural fullness (18,8%); and difficulty to hear, sometimes (43,8%). Concerning to the audiometric findings, 90,62% of the teachers did not have hearing losses, against 9,37% who did. Bilateral neurossensorial loss was present in 3,12%; increased audiometric thresholds 3kHz and 4kHz in 6,25%. The frequency of 6 kHz was the most reached by the audiometric notch, and half of the teachers had it in at least one hear. Conclusion: There was no statistic significant difference comparing audiometric incision with teachers complains or with time of profession and wok journey. Making physical education teachers aware the risks of electronic amplified music can offer to the hearing system and health in general, is fundamental